Heart-Rate Recovery at 1 Min After Exercise Predicts Response to Balloon Pulmonary Angioplasty in Patients With Inoperable Chronic Thromboembolic Pulmonary Hypertension - Zhang, Yi; Li, Xin; Luo, Qin; Zhao, Qing; Zeng, Qixian; Yang, Tao; Jin, Qi; Yan, Lu; Duan, Anqi; Ma, Xiuping; An, Chenhong; Xiong, Changming; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Dysfunction of autonomic nervous system plays an important role in the development of pulmonary hypertension. The present study aimed to investigate the interaction between balloon pulmonary angioplasty (BPA) and cardiac autonomic function by using heart-rate recovery at 1 min (HRR1) after exercise as a surrogate marker. Methods and Results We retrospectively enrolled 89 consecutive patients with inoperable chronic thromboembolic pulmonary hypertension who underwent BPA from May, 2018 to Jan, 2021. According to hemodynamics at follow-up, patients were categorized as BPA responders if they met one or both of the following criteria: (1) mean pulmonary arterial pressure ≤ 30 mmHg and (2) a reduction of pulmonary vascular resistance ≥ 30%. Compared with baseline, HRR1 tended to increase within 7 days after the first BPA session, and this improvement persisted at follow-up. HRR1 at baseline and at follow-up were associated with well-validated markers of CTEPH severity, including N-terminal pro-brain natriuretic peptide, mean pulmonary arterial pressure and pulmonary vascular resistance. Furthermore, the change of HRR1 from baseline to follow-up was also associated with the change of those variables. After adjustment for confounders, baseline HRR1 was still a strong independent predictor of BPA outcome. Receiver operator characteristic curve analysis showed that the cutoff value for HRR1 in predicting BPA outcome was 19 beats. Conclusions BPA could significantly improve HRR1, suggesting the alleviation of sympathovagal imbalance. Easily available and non-invasive HRR1 seems to be a useful tool in predicting outcome of BPA and dynamically monitoring the efficacy of BPA.